Diagnostic validity of premenstrual dysphoric disorder: revisited - Naik, Shalini S.; Nidhi, Yadav; Kumar, Krishan; Grover, Sandeep (Frontiers in Global Women's Health, 2023)
The World Health Organization (WHO) and American Psychiatric Association (APA) have recognised premenstrual dysphoric disorder (PMDD) as an independent diagnostic entity, legitimising the distress and socio-occupational impairment experienced by affected women. However, the biological validity of this diagnosis remains inexplicit. This illness has also been criticised for a feminist-led, sympathetic reaction to the modern cultural challenges of urban, literate, employed, high-functioning women. This article systematically reviews existing literature on PMDD using the criteria established by Robins and Guze for the validity of a psychiatric diagnosis (clinical description, laboratory study, exclusion of other disorders, follow-up study, and family study). Despite the early recognition of premenstrual syndrome (PMS) in the 1950s, the research has encountered challenges due to two groups of proponents viewing it with psychologising bias and medicalising bias. PMDD is currently understood as the most severe form of PMS, characterised by the presence of psychological features. Recent evidence suggests that PMDD perhaps has neurodevelopmental underpinnings (attention deficit hyperactive disorder, adverse childhood experiences) affecting the fronto-limbic circuit that regulates the emotions. In addition, the affected individuals exhibit an increased sensitivity to gonadal hormonal fluctuations as observed during premenstrual, pregnancy, and perimenopausal phases of life. The prevalence is comparable between high-income countries and low- and middle-income countries (LAMIC), refuting the notion that it mostly affects modern women. Instead, a greater prevalence is observed in LAMIC. Despite the fact that educated women possess knowledge regarding the importance of getting help, there is a prevalent issue of inadequate help-seeking behaviour. This can be attributed to the perception of seeking help as an isolating experience, which is influenced by profound internalised stigma and discrimination in the workplace. Future studies must aim to develop culturally validated assessment tools and more research to understand the life course of the illness, in addition to systematically examining for more biological validators (animal models, genetics, imaging, neurotransmitters).